The internalization of the value of Islamic Religious Education to students to prevent bulliying behavior in State High School 1 Sumberpucung - Sugiati Sugiati (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
State High School 1 Sumberpucung is a public school located in Sumberpucung distric of Malang regency. This school is a reference school for the people of Sumberpucung and other sub-distric around Sumberpucung because it has a myriad of achievements both academic and non-academic levels by teachers and students. With bulliying behavior among students today, the school hopes for the internalization of the value of Islamic Religious Education to students to prevent bulliying behavior . The purpose of this study is to discribe, analyze, and interpret:1) The value of Islamic religious Education are internalized in preventing bulliying behaviour in State High School 1 Sumberpucung, 2) The process of internalizing the values of Islamic religious Education in preventing bulliying behavior in State High School 1 Sumberpucung , 3) the internalization model of Islamic Religious Education values in preventing bulliying behavior in State High School 1 Sumberpucung . Researc uses a qualitative approach with this type of case study. The data source of this study is primary data derived from answers during interviews and secondaryndata and other data related to the study. Data collection methods use observation, interview and documentation techniques. Data analysis uses data reduction methods (condensation), presentation of data anda conclusion withdrawal. The results of the study show that: 1) The values of Islamic Religious Education that are internalized in preventing bulliying behaviour in State High School 1 Sumberpucung are values: I’tiqodiyah, amaliyah, khuluqiyah. 2) Internalization process islamic Religious education values used are modelling strategies, habituation strategies, advice giving strategies, promises and threats strategies (tarhib wa targhib), discipline strategies. 3) The internalization model of Islamic religious Education values used are structural models, formal models, mechanical models, organic models and initiative models